Coverage of deaths with medical certification in Peru, 2012 -2019 - Vargas-Herrera, Javier (2022)
The strengthening of civil registration and vital statistics (RCEV) systems is essential to assess the impact of health interventions and the effects of health emergencies. Peru faced the COVID-19 pandemic, in the process of strengthening the RCEV system, in which the implementation of SINADEF stood out, which allowed it to improve the quality and coverage of information on mortality. A compilation of information from various public information sources was carried out to calculate the coverage of mortality in Peru for the period 2012 to 2019. The coverage of deaths with medical certification rose from 57.65% in 2016 to 71.6% in 2019 and improved in all regions of Peru at the national level, additionally, online certification of deaths rose from 29% in 2017 to 86% in 2020. The SINADEF has made it possible to implement a rapid mortality surveillance system and measure the excess mortality that is occurring in the context of the pandemic.